Best Thai recipes: take a glimpse of the authentic Thai cuisine - Rachael Rayner ([Place of publication not identified] : [Publishers name not idntified], 2019)
In the book you will find 30 authentic Thai recipes. They are a mixture of main course, snacks, desserts, beverages, and side dishes. Thai cuisine is quite versatile in its ingredient choices. The ingredients are fresh and easily found. They try to incorporate herbs and chilies as much as possible in their everyday cooking. They try to limit their junk food consumption. Therefore, you will find less fried food in their cuisine.
Keywords: Thai Recipes; Thai Cuisine